Característica multimodal do fator de refletividade radar para sistema de precipitação: estudo do caso furacão Katrina - Lopes, Gerson Ernesto Varela (2014)
Weather Radar technology have been used for monitoring weather systems since the beginning of its development as a powerful instrument to detect, observe, and study precipitating structures (Battan, 1973; Sauvageot, 1992, among others). A set of radar data gathered over various sites of the US NEXRAD (Next Generation Weather Radar) S band radar network is used to analyze the probability distribution function (pdf) of the radar reflectivity factor (Z) of precipitation, P(Z). The probability distribution of the average reflectivity factor P(Zm) allows to find the possible values (limits) of reflectivity for the system and can thus characterize it in terms of its physical structure. Hurricane Katrina (August 2005) was an extraordinarily powerful hurricane, considered one of the most devastating natural disasters of the USA, not only by property damage, but mainly for the human losses (Knabb et al., 2005). Katrina complex genesis involved the interaction of a tropical wave, mid-tropospheric remnants of Tropical Depression 10, and an upper-tropospheric trough. Three radars were chosen to study Katrina’s physical characteristics (i.e., hydrometeors, convective vs stratiform features, rainbands) according to the hurricanes displacement: KLIX New Orleans (Louisiana), KBMX Birmingham (Alabama), and KNQA Memphis (Tennessee). Using IDV (Integrated Data Viewer – UNIDATA, UCAR) to visualize Katrina structure and MATLAB® to compute histograms of the empirical cumulative density function (ecdf), preliminary results demonstrate a co-existence of stratiform and convective precipitation. Due to the existence of different rainbands, reflectivity varies between ~10 to 45 dBZ, with some convective and stratiform peaks according to the hurricane strength. In all analyzed radar persists a similar behavior, i.e., in the early hours of observation the PDF tends to bimodality with approximate values of 15 and 23-25 dBZ, and later the trend is to unimodality. This fact is due to the approximation of the convective bands - primary, secondary - and far convective elements.